Курган эпохи ранней бронзыу села Григорьевка - Агульников, С.М.; Попович, С.С. (Материалы по археологии Северного Причерноморья, 2009)
In 1989 one tumulus of Early Bronze Age near village Grigorovka (Sangerei district Republic of Moldova) was excavated. There were 12 tombs. From this number the 11 tombs belonged to the Pit-Grave culture. The box-shaped vessel is of interest. It was founded in the grave of the late Pit-Grave culture. This vessel has an analogy in the Katacombnaya culture of the East part of North-Pontic region.